RANCANG BANGUN MONITORING LISTRIK PADA RUMAH BERBASIS IOT MENGGUNAKAN ESP32 - Wiesesha, Adhitya; Ridhoi, Ahmad (TEKNIKA, 2023)
In modern times the electric power system is a necessity that cannot be separated from human life. All human work and needs are highly dependent on electricity, especially household needs. The use of electrical energy can cause excessive use, which has an impact on increasing voltage, current, and power for electricity users, causing costs to not be minimized. Therefore, we need a tool that can monitor the use of electrical energy and is able to limit voltage, current and power even though the user of electrical energy is not at home. Monitoring that electricity users can use when they are not at home is IOT-based monitoring. Of course, for IOT-based monitoring, voltage sensors, current sensors, and MCU nodes with blynk are needed for monitoring displays. The voltage sensor uses the PZEM-004T which functions to read the voltage value, the current sensor which functions to read the current value in the load, and the NodeMCU uses ESP 32 as a WIFI module which functions as sending data to the server so that it can be viewed via the internet network. The test results of this tool functioning correctly can remotely monitor voltage, current and power values ​​that are displayed on cellphones by producing low error rates that occur on voltage, current and power.